Effects of a deep container on morpho-functional characteristics and root colonization in Quercus suber L. seedlings for reforestation in Mediterranean climate - Chirino, E.; Vilagrosa, A.; Hernández, E. I.; Matos, A.; Vallejo, V. R. (Forest Ecology and Management, 2008)
In the last decades, reforestation and afforestation programs are being carried out mainly with containerized seedlings. Container design determines the morphological and physiological characteristics of seedlings. However, container characteristics are often the same for plant species with very different growth strategies. The most commonly used nursery containers are relatively shallow and limit tap root growth; consequently, species relying on the early development of a long tap root to escape drought, such as those of the Quercus genus, might need to be cultivated in deep containers. The aim of this paper was to compare the morphological and physiological characteristics of Quercus suber L. seedlings cultivated in shallow containers (CCS-18, depth 18 cm) with seedlings cultivated in deep containers (CCL-30, depth 30 cm). Both container types used were made of high-density polyethylene, cylindrical in shape, open-bottomed, with a diameter of 5 cm, two kinds of vertical ribs on the inside wall showing a cultivation density of 318 seedlings/m2 . At the end of nursery culture, the seedlings cultivated in the CCL-30 deep container presented a longer tap root, higher shoot and root biomass and higher Dickson Quality Index (DQI). Moreover, the CCL-30 seedlings showed a higher root growth capacity (RGC), they reached deep substrate layers faster and they presented higher root hydraulic conductance. These morpho-functional advantages improved the CCL-30 seedling water status, which was expressed by higher stomatal conductance during an imposed drought period
Keywords: Forest tray; Hydraulic conductance; root system; Stomatal conductance

Effects of a deep container on morpho-functional characteristics and root colonization in Quercus suber L. seedlings for reforestation in Mediterranean climate - Chirino, E; Vilagrosa, A; Hernández, E I; Matos, A; Vallejo, V R (Forest Ecology and Management, 2008)
In the last decades, reforestation and afforestation programs are being carried out mainly with containerized seedlings. Container design determines the morphological and physiological characteristics of seedlings. However, container characteristics are often the same for plant species with very different growth strategies. The most commonly used nursery containers are relatively shallow and limit tap root growth; consequently, species relying on the early development of a long tap root to escape drought, such as those of the Quercus genus, might need to be cultivated in deep containers. The aim of this paper was to compare the morphological and physiological characteristics of Quercus suber L. seedlings cultivated in shallow containers (CCS-18, depth 18 cm) with seedlings cultivated in deep containers (CCL-30, depth 30 cm). Both container types used were made of high-density polyethylene, cylindrical in shape, open-bottomed, with a diameter of 5 cm, two kinds of vertical ribs on the inside wall showing a cultivation density of 318 seedlings/m2 . At the end of nursery culture, the seedlings cultivated in the CCL-30 deep container presented a longer tap root, higher shoot and root biomass and higher Dickson Quality Index (DQI). Moreover, the CCL-30 seedlings showed a higher root growth capacity (RGC), they reached deep substrate layers faster and they presented higher root hydraulic conductance. These morpho-functional advantages improved the CCL-30 seedling water status, which was expressed by higher stomatal conductance during an imposed drought period
Keywords: Forest tray; Hydraulic conductance; root system; Stomatal conductance

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G.; Obrador, J. J.; García, E.; Cubera, E.; Montero, M. J.; Pulido, F.; Dupraz, C. (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G; Obrador, J J; García, E; Cubera, E; Montero, M J; Pulido, F; Dupraz, C (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources

Root responses of Quercus ilex L. seedlings to drought and fire - Chiatante, D.; Di Iorio, A.; Scippa, G. S. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Drought treatments in holm-oak (Quercus ilex) seedlings induce variations in total root length, number of root apices, shoot/root dry weight, and root electrolyte leakage. When drought treatments last for more than 50 days a considerable number of fine lateral roots die, irrespective of branching order or distribution within the root system. Scorching of drought-treated seedlings induces a transient stimulation of root growth. These results indicate that root turnover is deeply affected during treatments, with survival of seedlings being entrusted to the tolerance of a number of roots situated in the deeper region of the root system. Activity of the meristematic tissue present within the apices of these surviving roots supports regeneration of above-ground lost organs during recovery. Knowledge of the mechanisms ensuring the survival of Mediterranean tree seedlings following drought and fire is useful for developing models of vegetation dynamics.
doi: 10.1080/11263500500160591doi: 10.1080/11263500500160591The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Drought; Quercus ilex; root system; seedlings; ﬁre

Root responses of Quercus ilex L. seedlings to drought and fire - Chiatante, D; Di Iorio, A; Scippa, G S (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Drought treatments in holm-oak (Quercus ilex) seedlings induce variations in total root length, number of root apices, shoot/root dry weight, and root electrolyte leakage. When drought treatments last for more than 50 days a considerable number of fine lateral roots die, irrespective of branching order or distribution within the root system. Scorching of drought-treated seedlings induces a transient stimulation of root growth. These results indicate that root turnover is deeply affected during treatments, with survival of seedlings being entrusted to the tolerance of a number of roots situated in the deeper region of the root system. Activity of the meristematic tissue present within the apices of these surviving roots supports regeneration of above-ground lost organs during recovery. Knowledge of the mechanisms ensuring the survival of Mediterranean tree seedlings following drought and fire is useful for developing models of vegetation dynamics.
doi: 10.1080/11263500500160591
Keywords: Drought; Quercus ilex; root system; seedlings; ﬁre

Anatomía y caracterización del sistema radicular del alcornoque - VERDAGUER, D; Molinas, M L (SCIENTIA gerundensis, 1992)
In this paper we describe the root system of a mature cork oak (Quercus suber L). The roots were excavated by hand methods, seccioned and weighed. Large sections were described anatomically and sections smaller than 10 mm of diameter by histological tecniques. The root system components were distributed into central root system (CRS) and peripheral root system (PRS). The CRS was located at the base of the tree and embraced an area of 1'5 m and a depth of 60 cm; it consisted of the root crown, thick horizontal or descending roots and thin roots. The PRS extended in a circle of 12 m in diameier. In the PRS, the thick roots were distributed more laxly and the thin roots predominated. At their basal portion, the descending roots were eccentric and eliptic and rapidly forked into two or more small- diameter branches. Grafting between root axes was frequent. The horizontal roots were perpendicular to the tree axis, they were quite circular and kept thickness more or less constant since they forked. Large-diameter root tips, white coloured were observed and their primary structure described. Neither on the root crown nor at the base of the roots, lateral huds were observed.
Keywords: Cork oak; Quercus suber L.; root; root anatomy; root system